Keputusan Investasi dan Profitabilitas terhadap Harga Saham pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2021–2024 - Laynita Sari; Mitra Prakusia Saogo (ARZUSIN, 2026)
The high volatility of stock prices in the property and real estate sector poses challenges for investors in predicting price movements and assessing firms’ fundamental performance. This study aims to analyze the effect of investment decisions and profitability on stock prices of property and real estate companies listed on the Indonesia Stock Exchange (Bursa Efek Indonesia, BEI) during the 2021–2024 period. A quantitative approach was employed with purposive sampling of 21 companies, resulting in 84 observational data points. Secondary data were collected from the official BEI website and analyzed using panel data regression with the aid of EViews 12 software. The results show that investment decisions do not have a significant effect on stock prices, whereas profitability has a positive and significant effect on stock prices. These findings indicate that investors are more responsive to firms’ earnings performance than to investment decisions as reflected in financial statements. The study concludes that improving profitability is a key factor in strengthening stock prices in the property and real estate sector and recommends that companies place greater emphasis on operational efficiency and profit management to enhance their investment appeal in the capital market.